Detection of Movement Intention for Operating Methods of Serious Games - Jung-Hyun Park; Ho-Sang Moon; Hyunggun Kim; Sung-Taek Chung (Applied Sciences, 2021)
In many post-stroke cases, patients show dysfunctions in movement, cognition, sense, and language, depending on the damaged area of the brain. Active and repetitive physical rehabilitation centered on the stroke-affected side is essential for effective and rapid neurological recovery of upper extremity dysfunction due to hemiplegia. A symmetric upper extremity trainer is utilized to assist the patient body, depending upon the degree of hemiplegia. In this study, we developed a novel balance handle as a symmetric upper extremity trainer capable of extension, flexion, pronation, and supination of the upper extremity. We collected the surface electromyogram (sEMG) signal data while the subjects were playing a serious game and recorded the electroencephalogram (EEG) signal data while the subjects were performing basic movements with the balance handle, to analyze the effectiveness of the device as an assistive tool for rehabilitation. The triceps brachii were activated during the extension movements, whereas the biceps brachii and deltoid muscles were activated during the flexion movements. With the balance handle, the peak event-related desynchronization (ERD) values were relatively lower while showing higher peak event-related synchronization (ERS) values compared to other types of operating methods, such as hand gripping and gamepad operation. Movement intention of tilting the balance handle for the α and β waves was clearly distinguished from the other tasks. These data demonstrated the potential of various applications using the developed proof-of-concept upper extremity trainer to bring out an excellent rehabilitative effect not only through muscle growth but also via identification of large movement intentions inducing brain activation exercise.